Keberadaan Fungi Pelarut Fosfat pada Tanah Bekas Erupsi Gunung Sinabung di Kabupaten Karo - Suryanti Saragih; Deni Elfiati; Delvian Delvian (Peronema Forestry Science Journal, 2015)
Merapi eruption produced clouds of volcanic material and heat. Volcanic material will close the land with a certain thickness. This will affect the physical, chemical and biological soil. This research was conducted to determine the presence of Phosphates Solubilizing Fungi in the soil of former eruption in Karo regency. The soil samples were taken in areas affected by the eruption at a depth of 0-5 cm and a depth of 5-20 cm, while in areas not affected by the eruption was taken at a depth of 0-20 cm. The results showed the similarities of fungi genus and the differences of fungi phosphate solvent affected by the eruption or land that is not affected by the eruption. There are 2 genus of fungi that are found in all depth of soil, there are Aspergillus and Penicillium. The number of fungi isolates obtained 10 isolates there are 7 isolates of Aspergillus and Penicillium are 3 isolates.Keywords : The eruption of Mount Sinabung, Phosphates Solubilizing Fungi, Phosphates